Peningkatan Kompetensi Guru dalam Pelaksanaan Evaluasi Pembelajaran di Sekolah Madrasah Aliyah YPP Jamanis Kabupaten Pangandaran: Pengabdian - Muthi, Ibnu; baharuddin; Muntaha; Yuli Sugiarti, Diyah; Apriliantoni; Listiowati; Lili Hamdani, Umat; Iqbal, Muhammad; Adnan Fahrezi, M.; Sandra, Yopfie; Irwansyah, Saripudin; Rafa, Juana; Atsyir Nujud, Ya’sub; Sidqia, Fanny (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The low competence of teachers in carrying out systematic and accountable evaluation of learning, which has an impact on the quality of assessment of student learning outcomes is a crucial problem in the world of Education. The purpose of this service is to increase the capacity of teachers through training on the preparation of evaluation instruments based on a systematic approach, focusing on validity, reliability, and accountability principles. The implementation method uses a combination of Forum Group Discussion (FGD), intensive assistance (offline and online), and the practice of preparing evaluation instruments. The results of the service showed that 76.2% of participants experienced a significant increase in evaluation competence, the formation of Teacher Learning Communities, and standardization of assessment systems in madrasahs. Implications of the program include strengthening the culture of data-based evaluation, increased accountability of learning, as well as replication model for madrasah. These findings confirm the importance of continuous mentoring and technology integration in the development of educational evaluation systems.